2004
DOI: 10.1161/01.str.0000110981.96204.64
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Carotid Plaque and Stenosis

Abstract: Background and Purpose-Women are relatively protected from cardiovascular events; they are 3 times as likely as men to survive to age 90 years. Although clinical trials show an excess of thrombotic events with estrogen/progestin hormone replacement therapy, much experimental and epidemiological evidence suggests that estrogen may have beneficial effects on endothelial function and atherosclerosis, raising the possibility of sex differences in arterial remodeling. We studied sex differences in carotid plaque an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
77
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(94 citation statements)
references
References 53 publications
14
77
1
2
Order By: Relevance
“…A partial explanation may involve the influence of sex hormones 22) . In their study, Iemolo et al 22) found that the prevalence of MetS-associated coronary heart disease in women aged 35 to 54 years was almost the same as that in the control group, whereas in women aged 55 to 74 years and in men aged 35 to 74, this prevalence was about twice that of the control group 23) . In several studies, estrogen was thought to be related to an improvement in traditional risk factors, such as elevated levels of lipoproteins 24,25) .…”
Section: Discussionmentioning
confidence: 99%
“…A partial explanation may involve the influence of sex hormones 22) . In their study, Iemolo et al 22) found that the prevalence of MetS-associated coronary heart disease in women aged 35 to 54 years was almost the same as that in the control group, whereas in women aged 55 to 74 years and in men aged 35 to 74, this prevalence was about twice that of the control group 23) . In several studies, estrogen was thought to be related to an improvement in traditional risk factors, such as elevated levels of lipoproteins 24,25) .…”
Section: Discussionmentioning
confidence: 99%
“…A duplex ultrasound study of 1686 patients with vascular disease, stroke, transitoric ischemic attack or asymptomatic carotid stenosis with a 5-year follow-up showed that plaque area is a stronger predictor for stroke than the degree of stenosis. In general, the incidence of carotid stenosis in men is more often and the plaque area is larger than in women [10]. Assessment of carotid plaques by duplex ultrasound revealed that a high ratio of fat to necrotic core, a thin or ruptured fibrinous cap, plaque haemorrhage and a larger wall thickness all are associated with a higher risk for an ischemic cerebrovascular event.…”
Section: Analysis Of Plaque Morphologymentioning
confidence: 99%
“…With no statically difference between CAS and medically treated group (p>0.05). According to disability as regard MRS at presentation in each group, 8 (26.6%) patients in CAS had MRS 0.22 (73.4) patients had MRS 1-2 and no patients had MRS 3, while in medically treated group 4 (20%) patients had MRS 0, 16 (80%) patients had MRS 1-2 and no patients had MRS 3,with no statically difference between CAS and Medically treated group (p>0.05).As regard NIHSS at presentation, 8 (26.7%) patients in CAS group were normal (NIHSS was 0),7 (23.3%) patients had mild stroke (NIHSS 1-5),15 (50%) patients had moderate stroke (NIHSS 6-15) and no patient had moderate to sever (NIHSS [16][17][18][19][20][21][22][23][24][25] or sever stroke (NIHSS 26-42), while in medically treated group 4 (20%) patients were normal, 7 (35%) patients had mild stroke, 9 (45%) patients had moderate stroke and no patient had moderate to sever or sever stroke. With no statically difference between CAS and medically treated group (p>0.05).…”
Section: Resultsmentioning
confidence: 92%
“…Sex hormones seem to play a funda-mental protective role in women through widespread actions, affecting endothelial function, lipid homeostasis, and cardiovascular risk factor reduction [18]. Moreover, some authors claim that estrogens might have plaque stabilization properties and effects on inflammatory status [19].…”
Section: Discussionmentioning
confidence: 99%